All or (almost) nothing? The influence of information cost and training on information selection and the quality of decision-making - Caroline Baethge; Marina Fiedler (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2016)
The following experiment examines the influence of cost of information and training on the quality of individual investment decisions. We expand upon the existing behavioral literature by proposing a new scenario experiment which enables us to study individual and institutional factors influencing the selection and processing of information that lead to an investment decision. The amount and type of information used, as well as the time of information processing of individual decision-makers will be measured by subjects' interaction in the experimental task. Furthermore, we examine whether or not cost of information and training indeed influence the quality of (investment) decision-making. The results suggest that training is crucial to the amount and type of information used as trained individuals make better investment decisions, using the most relevant information.
Keywords: 650; training; cost of information; information selection; quality of decision-making; performance